The Arts of Lobbying: Scrutinizing the Functions of Interactional Meta-discourse in Model United Nations Conferences - Sahila Rizqy, Muhammad Hifni; Fitriyah, Ulil (Master Program in Linguistics, Diponegoro University, 2023)
This study explores how speakers use interactional markers in the diplomatic speech Model United Nations Conference. We used a discourse analysis approach focusing on the meta-discourse markers; the analyzed data comes from the speech utterances based on 10 representative delegates. The data was taken on 27-28 March during the conference day. The five research classifications are hedges, Boosters, Attitude Markers, Engagement, and Self-mentions. The result reveals that the speakers use 280 interactional markers. Besides, the speaker's use of interactional markers might designate a tendency that would impact the audience's agreement on the topic.